2007
DOI: 10.1002/sce.20209
|View full text |Cite
|
Sign up to set email alerts
|

Identity development as a lens to science teacher preparation

Abstract: Concepts and findings from research on identity development are employed to better understand why current science teacher preparation programs are failing to prepare teachers who are able and choose to implement the vision for science education articulated in professional standards. Identity theory is used as a theoretical lens to make sense of and better address some of the unique challenges of becoming a reform‐minded science teacher, a professional identity that does not reflect the common norm in the profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
205
0
21

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 287 publications
(233 citation statements)
references
References 55 publications
(59 reference statements)
7
205
0
21
Order By: Relevance
“…Yavuz Saka, Sherry Southerland, Julie Kittleson, and Todd Hutner (2013) call the identity of such teachers 'reform-minded'. However, as April Lynn Luehmann (2007) shows, it is not an easy task to become a reform-minded science teacher. It is a complex process of identity development-a process of forming and reforming oneself.…”
Section: Science Teacher Identitymentioning
confidence: 99%
“…Yavuz Saka, Sherry Southerland, Julie Kittleson, and Todd Hutner (2013) call the identity of such teachers 'reform-minded'. However, as April Lynn Luehmann (2007) shows, it is not an easy task to become a reform-minded science teacher. It is a complex process of identity development-a process of forming and reforming oneself.…”
Section: Science Teacher Identitymentioning
confidence: 99%
“…In fact, one of the purposes of the REFLECT rubric was to provide a framework for formative feedback that could support students in developing their reflective capacity (Wald et al, 2012). It is also important to point out that professional identity construction is not a stable, straightforward process (Dall'Alba, 2009;Luehmann, 2007), and thus reflective writing done in service of this task will likely reflect this instability. Our preliminary research on reflection and identity development supports this, as results suggested that reflective abilities varied within individual participants DOCUMENTING DESIGN IDEAS 14 across the semester, particularly in participants who fell in the lower tiers of reflective ability (Author, 2014).…”
Section: General Patterns In Student Reflectionmentioning
confidence: 99%
“…It is commonly thought that inspiration strikes when intense work sessions are alternated with periods of mental relaxation away from the design problem (Cross, 2007) or, similarly, after a period of incubation or shift in context, often after a period of feeling blocked or fixated on an unworkable idea (Smith, 2003). Other studies have examined how stimuli may trigger the emergence of design ideas or influence the content of those ideas; these include textbased stimuli, visual stimuli, subliminal stimuli, verbal or conversational stimuli, and other idea DOCUMENTING DESIGN IDEAS 4 generation activities (Cai, Do, and Zimring, 2009;Chandrasekera et al, 2012;Goldschmidt & Sever, 2010;Gonçalves, Cardoso, & Badke-Schaub, 2014;Perttula & Sipilä;2007;Salter & Gann, 2002). Still others have identified the end users as the primary trigger for design ideation, with designers attempting to reduce the design problem complexity by empathizing with learners and better anticipating the learning experience (Rapanta & Cantoni, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Gee (2005) articulates, it is important to keep in mind that, while one's participation within a given Discourse is necessary in order for a new identity to develop, it is in the interpretation or recognition of that participation, by self or others, that identities are formed. In another article, I extended this discussion by considering this participation and recognition work specifically in the case of the professional learning of reform-minded science teachers (Luehmann 2007).…”
Section: Theoretical and Empirical Foundationsmentioning
confidence: 99%